Personality and self-employment: A journey into the craft's way of doing business - Petrik Runst; Jörg Thomä (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2023)
The renewed scholarly interest in the craft-based mode of competition, work, learning and innovation suggests that there are some unique aspects of the craft's way of doing business. Using a large panel data set, the present paper takes a closer look at this issue by examining the personality characteristics of business owners. Our results confirm that an individual's personality affects the likelihood of self-employment, but certain traits have a different effect in the case of crafts vis-à-vis non-crafts. We interpret this as evidence for the specificity of the 'crafts' at the fundamental level of human personality. Thus, personality traits can influence self-employment decisions differently, depending on the sector or field of entrepreneurship. The paper concludes with implications for policy and research.
Keywords: D91; L26; M13; M21; 330; Crafts; Self-employment; Personality; crafts entrepreneurship; craftsmanship